Senile plaque neurites in Alzheimer disease accumulate amyloid precursor protein. - Cras, P (1991)
Senile plaques are polymorphous beta-amyloid protein deposits found in the brain in Alzheimer disease and normal aging. This beta-amyloid protein is derived from a larger precursor molecule of which neurons are the principal producers in brain. We found that amyloid precursor protein (APP)-immunoreactive neurites were involved in senile plaques and that only a subset of these neurites showed markers for the abnormal filaments characteristic of neurofibrillary pathology. In the neocortex of nondemented individuals with senile plaques but spared of neurofibrillary pathology, dystrophic neurites in senile plaques showed only APP accumulation. In contrast, in the brains of Alzheimer patients, virtually all APP-immunoreactive neurites also showed immunoreactivity with ubiquitin, tau, and phosphorylated neurofilaments. The presence of tau and neurofilament epitopes in dystrophic neurites in senile plaques was correlated with the extent of neurofibrillary pathology in the surrounding brain tissue. Accumulation of APP and the formation of neurofibrillary pathology in senile plaque neurites are therefore distinct phenomena. Our findings suggest that APP accumulation in senile plaque neurites occurs prior to tau accumulation and is therefore more closely related to appearance of neuritic dystrophy.